Alfvén eigenmodes and fast ion transport in negative triangularity DIII-D plasmas. (27th June 2019) - Van Zeeland, M.A.; Collins, C.S.; Heidbrink, W.W.; Austin, M.E.; Du, X.D.; Duarte, V.N.; Hyatt, A.; Kramer, G.; Gorelenkov, N.; Grierson, B.; Lin, D.; Marinoni, A.; et al.
Abstract: The first energetic particle experiments in negative triangularity tokamak plasmas have been carried out on DIII-D. Alfvén eigenmode (AE) activity and associated fast ion transport comparable to that in positive triangularity is observed during the current ramp portion of all plasmas with early beam heating indicating negative triangularity does not confer a special advantage with respect to AE induced transport. In these discharges, a range of mode activity driven by the sub-Alfvénic ( ) 80 kV neutral beams is found including beta induced Alfvén acoustic eigenmodes, beta induced Alfvén eigenmodes, reversed shear Alfvén eigenmodes (RSAEs) and toroidicity induced Alfvén eigenmodes (TAEs). Mode intermittency and possibly chirping appears to be more common than comparable positive triangularity and/or oval discharges but overall, the unstable spectra and mode amplitudes observed on magnetics, CO2 interferometry, and electron cyclotron emission in a set of matched positive and negative triangularity cases at moderate beam power is similar. Large levels of Alfvén eigenmode induced fast ion transport are found in both positive and negative triangularity with up to central fast ion pressure deficits relative to classical predictions early during the current ramp phase for discharges with 3 MW injected 80 kV neutral beam power. The deficit in both cases is reduced toward zero as the current penetrates and eventually reaches classical levels during current flattop with . Fast ion transport in negative triangularity plasmas measured using a beam modulation technique show very similar levels to those measured in oval plasmas over the range of tested beam powers ( –7 MW). This similarity is found despite quite different unstable spectra in the highest beam power case where a mixture of coherent and quasi-coherent modes in the TAE frequency range are observed in negative triangularity and a spectrum of more typical narrowband TAEs and RSAEs is observed for the oval plasmas.